1997
DOI: 10.1002/jhrc.1240200202
|View full text |Cite
|
Sign up to set email alerts
|

Adulteration or natural variability? enantioselective gas chromatography in purity control of essential oils

Abstract: SummaryThe potential of enantioselective capillary gas chromatography with modified cyclodextrins as chiral stationary phases for authenticity control is demonstrated for a selection of economically important essential oils. Adulteration can be easily detected in cases where enantiomerically pure constituents are present in natural oils. In cases of (naturally) varying enantiomeric compositions of chiral constituents, enantioselective gas chromatography may prove insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 18 publications
3
23
0
1
Order By: Relevance
“…Specifically, these enantiomers were (-)-menthone, (-)-neomenthol, (-)-menthol, and (+)-isomenthol. This is in agreement with data previously found for a number of samples in our laboratory by employing solid phase microextraction (SPME) [19] as well as by other authors using different analytical techniques [20][21][22]. Although the peak areas obtained (Table 1) were similar when applying any of the set of values of the tested parameters, 208C and 3 min were finally selected as the PTV temperature and the purge time, respectively, since they provided acceptable areas also showing high effectiveness in solvent elimination.…”
Section: Resultssupporting
confidence: 93%
“…Specifically, these enantiomers were (-)-menthone, (-)-neomenthol, (-)-menthol, and (+)-isomenthol. This is in agreement with data previously found for a number of samples in our laboratory by employing solid phase microextraction (SPME) [19] as well as by other authors using different analytical techniques [20][21][22]. Although the peak areas obtained (Table 1) were similar when applying any of the set of values of the tested parameters, 208C and 3 min were finally selected as the PTV temperature and the purge time, respectively, since they provided acceptable areas also showing high effectiveness in solvent elimination.…”
Section: Resultssupporting
confidence: 93%
“…Although a number of articles on the enantiomeric composition of some menthol isomers have previously been published by other authors [13][14][15], in most cases the reported studies refer to essential oils from Mentha species instead of to the plant material. Moreover, multidimensional chromatographic techniques have been so far mainly applied [15], thus demanding a careful and sometimes complex optimisation to be done before the analysis can be performed.…”
Section: Introductionmentioning
confidence: 93%
“…In all cases, the MS was set for a full scan from 40 to 300 mass units at an interval of 0.5s and a scan speed of 500amu s -1 . Linalool chirality (König et al, 1997) was determined on a Shimadzu GC-17A equipped with a flame ionization detector, using a 25m, 0.25mm inner diameter Lipodex-E column (Macherey-Nagel, Düren, Germany) with an isocratic oven temperature of 55°C and a flow rate of 2mlmin -1 .…”
Section: Volatile Sampling and Gcms Analysismentioning
confidence: 99%